Viajar e beber. Os vinhos cistercienses de Alcobaça (Portugal) na literatura de viagens - Maduro, António (2012)
The Cistercian Monastery of Alcobaça was the target of interest to scholarly travelers that in the eighteenth and nineteenth visited Portugal and stayed long enough to extend the tour beyond the geographical belt of the capital. With this visit, they sought to appreciate the architecture and art, with emphasis on the tombs of Pedro and Inês, whose history was written. Travellers of a higher status beneﬁted from the monastic hostel facilities, their table and their nectars. The travel literature they produced is of particular importance to evaluate the architectural transformations of buildings, feel the life of the Abbey, their habits, customs and rituals, understand the organization of the productive landscape. The vineyard and wine are signiﬁcant references in the descriptions. It’s the vineyards of the monastic enclosure and the Gafa’s “relego”, the grandeur of the winery and wine quality that they regard as the best in Europe.